(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The food and beverage industry includes restaurants, cafeterias, cafés, fast-food joints, pubs, delis, food manufacturing operations, catering businesses, food transportation services, and more.